Purple, stiff lesions resembling varicose veins on lower limb: certainly consider Kaposi sarcoma - Cingoz, Faruk; Arslan, Gokhan; Cicek, Ali Fuat; Oz, Bilgehan Savas (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Kaposi’s sarcoma (KS) typically presents multiple cutaneous lesions of the lower extremities. Lesions can rarely mimic varicose veins without venous insufficiency, vascular or stasis ulcers. As the initial diagnosis of KS is generally determined clinically, a high index of suspicion and palpation of lesions are necessary for all patients with atypical presentations of varicose-like lesions of lower extremities. Tissue biopsy with histological analysis is essential for all uncertain lesions. This is a case of KS occurring in a 79-year-old man who presented with indurated vascular plaques resembling varicose veins on the right foot.